PENGARUH HANDS ON MINDS ON ACTIVITY TERHADAP HASIL BELAJAR MELALUI INKUIRI TERBIMBING - Wanda Kurniawan; Chandra Ertikanto; Wayan Suana (Jurnal Pembelajaran Fisika, 2017)
This experimental study aims to determine the effect of hands-on minds on activity against students learning outcomes through guided inquiry. The experimental design is a one-shot case study, the population was that all of class X SMAN 2 Metro on even semester of academic year 2016/2017. Samples were students of class X IPA 2 were taken using cluster random sampling. The results of simple linear regression test is concluded that there is a positive and significant correlation between hands on minds on activity of the student learning outcomes in the cognitive domain through guided inquiry. The magnitude of the effect of hands-on minds on activity against students learning outcomes in the cognitive domain through guided inquiry amounted to 64.5 %.Penelitian eksperimen ini bertujuan untuk mengetahui pengaruh hands on minds on activity terhadap hasil belajar siswa melalui inkuiri terbimbing. Desain penelitian yang digunakan adalah one-shot case study, dengan populasi seluruh siswa kelas X SMA Negeri 2 Metro semester genap tahun ajaran 2016/2017. Sampel penelitian adalah siswa kelas X IPA 2 yang diambil dengan teknik Cluster Random Sampling. Berdasarkan hasil uji regresi linear sederhana diperoleh kesimpulan bahwa terdapat pengaruh positif dan signifikan antara hands on minds on activity terhadap hasil belajar siswa dalam ranah kognitif melalui inkuiri terbimbing. Besarnya pengaruh hands on minds on activity terhadap hasil belajar siswa dalam ranah kognitif melalui inkuiri terbimbing sebesar 64,5 %.Kata kunci: Hands On Minds On Activity, Hasil Belajar, Inkuiri Terbimbing